2017
DOI: 10.1039/c7nr04832g
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent mesoporous silica nanoparticles photo-delivering nitric oxide with carbon dots as fluorescence reporters

Abstract: Amino-terminated mesoporous silica nanoparticles embedding carbon dots (MSCD) formed by calcination were functionalized with a nitric oxide (NO) photodonor (1) to give a robust MSCD-1 conjugate. The intense fluorescence of MSCDs was strongly quenched in MSCD-1 by effective energy transfer. Visible light excitation of MSCD-1 liberates NO, suppresses the energy transfer mechanism and leads to concomitant fluorescence restoration of the MSCD scaffold, which acts as an optical reporter for the released NO. The MSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…10 nm blue-shifted if compared to that observed for the free NOPD in aqueous medium (see spectrum in Scheme 1, for sake of comparison), probably as a result of the different environment experienced by this chromogenic unit into the pore of the silica scaffold. This finding is in excellent agreement to what we recently observed for the same NOPD anchored on similar MSNs [36]. Note that, the introduction of the NOPD functionality into the nanoscaffold did not affect the particles size whose diameter was still of ~100 nm.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…10 nm blue-shifted if compared to that observed for the free NOPD in aqueous medium (see spectrum in Scheme 1, for sake of comparison), probably as a result of the different environment experienced by this chromogenic unit into the pore of the silica scaffold. This finding is in excellent agreement to what we recently observed for the same NOPD anchored on similar MSNs [36]. Note that, the introduction of the NOPD functionality into the nanoscaffold did not affect the particles size whose diameter was still of ~100 nm.…”
Section: Resultssupporting
confidence: 92%
“…Mesoporous silica nanoparticles (MSNs) are very suitable scaffolds to this end due to their high loading capacity, ease of surface functionalization, good biocompatibility, and satisfactory light transparency [26,27,28,29,30]. Moreover these inorganic scaffolds have been extensively used as excellent carrier for (i) conventional chemotherapeutics to reverse MDR [31], (ii) PDT agents alone and in combinations with chemotherapeutics [32,33,34], and (iii) spontaneous NO donors [35] and NOPD [36].…”
Section: Introductionmentioning
confidence: 99%
“…Schoenfisch and coworkers [102], among others [103], have used silica nanoparticles as a delivery method for NO-releasing compounds. Several recent studies (29,104,105) have demonstrated the use of similar silica-based NPs for photoNORM and photoCORM delivery agents. As will be discussed in the next section, Garcia et al (29) prepared mesoporous silica NPs with a NIR-photoactive core consisting of a upconverting NP (UCNP Figure 6.…”
Section: Polymer Metallic and Other Nanomaterials Platformsmentioning
confidence: 99%
“…However, their use is often limited because of reduced water solubility, photostability, prolonged cutaneous photosensitivity, and low selectivity [ 104 ]. For this region, different approaches have been investigated to combine photosensitizing drugs with other carriers such as liposomes [ 105 ], polymer nanoparticles [ 106 , 107 ], gold nanoparticles [ 108 ], carbon nanotubes [ 109 ], graphene’s [ 110 , 111 ] and carbon nanoparticles [ 112 , 113 ]. Recently, Huang et al [ 114 ] prepared a novel theranostic system based on chlorin e6-conjugated C-dots (C-dots-Ce6).…”
Section: Cds For Cancer Therapymentioning
confidence: 99%